Reactions to Dream Content: Continuity and Non-continuity - Kahn, David (Frontiers in Psychology, 2019)
Although dream content may at times be quite outlandish or illogical, the dreamer’s reactions to these events are not outlandish or illogical. Our study shows that the dreamer’s reaction to people and events are similar to what they would have been in wake life. There is continuity between the reactions of the dream and wake-self, even though situations my arise that aren't likely or possible in wake life. For example, a dream may include people and places that span different times that are weaved together as if they were occurring in the moment. Further, the behavior of the dream-self is often different than that of the wake-self. When this happens there is a non-continuity between the behavior of the dream and wake-self. Thus, there is both continuity and non-continuity between the dream and wake-self. Continuity in reactions and non-continuity in the kinds of situations and behaviors occurring while dreaming. This affords the dream-self with novel experiences that elicit reactions that are similar to how its wake-self would react.